Sul Ross, soldier, statesman, educator - Benner, Judith Ann, 1942- (Centennial series of the Association of Former Students, Texas A & M University, 1983)
Chronicles the life of Lawrence Sullivan Ross and discusses his childhood in the Iowa Territory, his dedication to working for the state of Texas, his career as president of Texas A & M College, and other related topics.